Soya agricultural waste as a rich source of isoflavones - Carneiro, Ariadne Magalhães [UNESP]; Moreira, Eduarda Antunes; Bragagnolo, Felipe Sanchez [UNESP]; Borges, Maiara Stefanini [UNESP]; Pilon, Alan Cesar; Rinaldo, Daniel [UNESP]; Funari, Cristiano Soleo [UNESP] (Elsevier, 2020)
Soybeans are among the world's major crops responsible for food and biodiesel production, as well as a major source of isoflavones – a class of high value-added bioactive compounds. As estimated 460 million tonnes of soya residues (branches, leaves, roots, and pods) will be produced in the 2018/2019 harvest, and 20–40% of this waste must be removed from the field to ensure soil quality and minimize environmental impacts. This work investigated the potential occurrence and content of isoflavones in soya agricultural waste collected directly from the ground after mechanically harvesting. We also assessed the extraction performances of ethanol and acetone for these materials as an alternative to acetonitrile, a problematic solvent from an environmental point of view. Considerable amounts of isoflavones were found in soya agricultural waste collected directly from the ground when compared to soybeans (2.71 ± 0.27, 0.57 ± 0.1, 0.30 ± 0.05 and 2.09 ± 0.24 kg of isoflavones/tonne of leaves, branches, pods, and soybeans, respectively). The greener ethanol and acetone performed well for a broad range of compounds. This is an example in which appreciable amounts of high value-added compounds are wasted. Since isoflavones are considered phytoestrogens, their recovery from part of this waste might avoid potential contamination of soil and groundwater.
Keywords: Apigenin; Bioeconomy; Biorefinary; Green chemistry; Phytoestrogen; Sustainable farm